Confirmative biophilic framework for heritage management. - Hung-Ming Tu (PLoS ONE, 2022)
Heritage managers often reuse heritage sites to attract tourists and conserve the sites. Not all adaptive heritage reuses achieve sustainable development. Biophilia is an innate, biological tendency to be close to natural and cultural elements, which may be a critical motivation for achieving sustainable heritage management. Past studies used qualitative and quantitative methods to extract participants' pull and push motivations toward heritage tourism and captured the six motivations of the biophilia framework that should be confirmed: heritage architecture; art activity; wide nature; regional attraction; recreational benefits; and long-term values. The purpose of this study was to conduct a confirmatory factor analysis to test the biophilia framework for understanding biophilic heritage tourism. A questionnaire with 18 items of heritage tourism motivation was used to explore the purpose of this study. A total of 193 valid questionnaires were obtained. Confirmatory factor analysis was used to examine the six motivations of the biophilia framework. The results indicated that heritage tourism motivation consisted of a second-order six-factor structure with high validity and reliability. These six dimensions reflected the biophilic requirements and provided a biophilic planning principle to achieve sustainable heritage management to satisfy the needs of the participants.